Small RNAs of the halophilic archaeon Haloferax volcanii. (20th January 2009) - Soppa, Jörg; Straub, Julia; Brenneis, Mariam; Jellen-Ritter, Angelika; Heyer, Ruth; Fischer, Susan; Granzow, Michaela; Voss, Björn; Hess, Wolfgang R.; Tjaden, Brian; Marchfelder, Anita
Abstract : In recent years, sRNAs (small non-coding RNAs) have been found to be abundant in eukaryotes and bacteria and have been recognized as a novel class of gene expression regulators. In contrast, much less is known about sRNAs in archaea, except for snoRNAs (small nucleolar RNAs) that are involved in the modification of bases in stable RNAs. Therefore bioinformatic and experimental RNomics approaches were undertaken to search for the presence of sRNAs in the model archaeon Haloferax volcanii, resulting in more than 150 putative sRNA genes being identified. Northern blot analyses were used to study (differential) expression of sRNA genes. Several chromosomal deletion mutants of sRNA genes were generated and compared with the wild-type. It turned out that two sRNAs are essential for growth at low salt concentrations and high temperatures respectively, and one is involved in the regulation of carbon metabolism. Taken together, it could be shown that sRNAs are as abundant in H. volcanii as they are in well-studied bacterial species and that they fulfil important biological roles under specific conditions.